Simultaneous quantitative and qualitative analysis of aliskiren, enalapril and its active metabolite enalaprilat in undiluted human urine utilizing LC‐ESI‐MS/MS. (2nd May 2014) - Burckhardt, Bjoern B.; Tins, Jutta; Laeer, Stephanie
ABSTRACT The benefit–risk ratio of combined blocking by the direct renin inhibitor aliskiren and an angiotensin‐converting enzyme inhibitor (e.g. enalapril) on the renin–angiotensin–aldosterone system is discussed. No method was available for simultaneous determination of both drugs in urine. A novel sensitive method for simultaneous quantification in undiluted human urine was developed which enables systematic pharmacokinetic investigations, especially in poorly investigated populations like children. Matrix effects were clearly reduced by applying solid‐phase extraction followed by a chromatographic separation on XselectTM C18 CSH columns. Mobile phase consisted of methanol and water, both acidified with formic acid. Under gradient conditions and a flow rate of 0.4 mL/min the column effluent was monitored by tandem mass spectrometry with electrospray ionization. Calibration curves were constructed in the range of 9.4–9600 ng/mL regarding aliskiren, 11.6–12000 ng/mL for enalapril and 8.8–9000 ng/mL for enalaprilat. All curves were analyzed utilizing 1/x2‐weighted quadratic squared regression. Intra‐run and inter‐run precision were 3.2–5.8% and 6.1–10.3% for aliskiren, 2.4–6.1% and 3.9–7.9% for enalapril as well as 3.1–9.4% and 4.7–12.7% regarding enalaprilat. Selectivity, accuracy and stability results comply with current international bioanalysis guidelines. The fully validated method was successfully applied to a pharmacokinetic investigation in healthy volunteers. Copyright © 2014 John Wiley & Sons, Ltd.